THE EFFECT OF PROFITABILITY RATIO AND MARKET RATIO ON STOCK PRICES IN INSURANCE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR PERIOD OF 2019 TO 2023 - ,; , (Bilancia : Jurnal Ilmiah Akuntansi; Vol 9 No 2 (2025): Bilancia : Jurnal Ilmiah Akuntansi, 2025)
This study aims to analyze the effect of profitability ratios which consist of Return on Assets and Return on Equity and market ratios which consist of Price Earning Ratio and Earning Per Share on Stock Prices of Insurance Companies listed on the Indonesia Stock Exchange for the period of 2019 to 2023. The population in this study were all Financial Sector Companies in the Insurance Sub-Sector listed on the Indonesia Stock Exchange (IDX) in 2019-2023, totaling 18 companies. The sample in this study was taken using a purposive sampling technique, where according to the sample criteria, 17 companies were obtained, so the number of samples in this study was 85 samples. Data analysis in this study used the multiple linear regression analysis method and been processed by SPSS. The results of the study showed that Return on Assets had a negative and insignificant effect on Stock Prices, Return on Equity had a positive and insignificant effect on Stock Prices, Price Earning Ratio had a positive and significant effect on Stock Prices and Earning Per Share had a positive and significant effect on Stock Prices in Insurance Companies listed on the Indonesia Stock Exchange for the 2019-2023 Period. Penelitian ini bertujuan untuk menganalisis pengaruh rasio profitabilitas yang terdiri dari Return on Assets dan Return on Equity serta rasio pasar yang terdiri dari Price Earning Ratio dan Earning Per Share terhadap Harga Saham Perusahaan Asuransi yang terdaftar di Bursa Efek Indonesia Periode 2019-2023. Populasi dalam penelitian ini adalah seluruh Perusahaan Sektor Keuangan Sub Sektor Asuransi yang terdaftar di Bursa Efek Indonesia (BEI) Tahun 2019-2023 yang berjumlah 18 perusahaan. Sampel dalam penelitian ini diambil dengan teknik purposive sampling, dimana sesuai dengan kriteria sampel didapatkan adalah sebanyak 17 perusahaan, sehingga jumlah sampel dalam penelitian ini adalah sebanyak 85 sampel. Analisis data dalam penelitian ini menggunakan metode analisis regresi linear berganda dengan bantuan SPSS. Hasil penelitian menunjukkan bahwa Return on Assets berpengaruh negatif dan tidak signifikan terhadap Harga Saham, Return on Equity berpengaruh positif dan tidak signifikan terhadap Harga Saham, Price Earning Ratio berpengaruh positif dan signifikan terhadap Harga Saham dan Earning Per Share berpengaruh positif dan signifikan terhadap Harga Saham pada Perusahaan Asuransi yang terdaftar di Bursa Efek Indonesia Periode 2019-2023.